National Trends in Antidepressant, Benzodiazepine, and Other Sedative-Hypnotic Treatment of Older Adults in Psychiatric and Primary Care - Maust, Donovan T. (J Clin Psychiatry, 2017)
OBJECTIVE: To describe how use of antidepressants, benzodiazepines, and other anxiolytic/sedative-hypnotics among older adults (age ≥65) has changed over time among visits to primary care providers and psychiatrists in the United States. METHOD: Data came from the National Ambulatory Medical Care Survey (years 2003–2005 and 2010–2012), a nationally-representative cross-section of outpatient physician visits. Analysis focused on visits to primary care providers (n=14,282) and psychiatrists (n=1,095) at which an antidepressant, benzodiazepine, or other anxiolytic/sedative-hypnotic was prescribed, which were stratified by demographic and clinical characteristic (including ICD-9-CM diagnosis) and compared across study intervals. Odds of medication use were calculated for each stratum, adjusting for demographic and clinical characteristics. RESULTS: The visit rate by older adults to primary care providers where any of the medications were prescribed rose from 16.4% to 21.8% (AOR 1.43, p<0.001), while remaining steady among psychiatrists (75.4% v. 68.5%; AOR 0.69, p=0.11). Primary care visits rose for antidepressants (9.9% to 12.3%; AOR 1.28, p=0.01) and other anxiolytic/sedative-hypnotics (3.4% to 4.7%; AOR 1.39, p=0.01), but the largest growth was among benzodiazepines (5.6% to 8.7%; AOR 1.62, p<0.001). Among patients in primary care, increases primarily occurred among men, non-Hispanic white patients, and both those with pain diagnoses as well as those without any mental health or pain diagnoses. CONCLUSION: From 2003–2012, use of the most common psychotropic medications among older adults seen in primary care increased, concentrated among patients with no mental health or pain diagnosis. As the population of older adults grows and receives mental health treatment in primary care, it is critical to examine the appropriateness of psychotropic use.